Penggunaan ICT dalam Penyusunan Modul Statistika - Tri Hidayati; Ita Handayani; Ines Heidiani Ikasari (Teknik Informatika Universitas Pamulang, 2018)
In this study, the objectives to be achieved are teaching material products in the form of information technology-based statistical modules (Information and communication technology). This study uses the development of the ADDIE model in the preparation of the module. The ADDIE model consists of analysis (analysis), design (design), development (development), implementation (implementation) and the last is evaluation (evaluation). In the ADDIE model, the module developed contains valid, practical and effective criteria. Validity criteria refer to the validity of experts and practitioners. For the practicality of modules developed, based on the instrument in the form of a questionnaire. While for module effectiveness, it can be seen from the value of student achievement. The results of this study indicate that the modules developed meet valid criteria which fall into the very good category. For the module practicality criteria, the research shows that the module falls into a very good category based on the observations of the implementation of lecturers' learning and assessment. Based on student responses, the developed statistical modules fall into the good category. As for the effectiveness category, based on student achievement, the module can be classified as effective.